PENGARUH LATIHAN KEGEL TERHADAP INKONTINENSIA URINE PADA LANSIA DI PANTI SOSIAL TRESNA WHERDA MECI ANGI BIMA - Dahlan D.A Dahlan D.A (poltekkes kemenkes mataram, 2014)
Abstract: Incontinence urine is health problems quite often be found in people aged advanced, Especially of women.Incontinence of urine is elimination of urine from the bladder an uncontrolled or occurring outside desire. Gymnastic kegel is gymnastics to strengthen pelvic muscles or calisthenics which aims to strengthen muscle basic pelvic muscles pubococcygeal especially of a muscle, So that it can strengthen muscles of the urinary tract.Exercise or gymnastic kegel has long been used to treat ( Nygaard, 2010).Research is aimed to know the influence of exercise kegel against incontinence of urine in elderly inhabitant of panti social tresna werdha meci angi bima. By using the method quasi experiment with a design research non-randomized one-group pretest posttest design. The withdrawal of samples conducted in purposive for the elderly experiencing of sampling the whole incontinence of urine in panti social Tresna Werdha Meci Angi Bima.The results of research showing absence of difference between frekwensi meaningfui micturition before exercise kegel with frekwensi micturition after exercise kegel with p value = 0,001 ( p value & it; 0.05 ) with having value as z -3,742. Based on these results can be concluded that the exercise kegel to a decrease in frekwensi micturition on elderly.